2015
DOI: 10.1503/cjs.002615
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial to investigate the effect of metal clips on early migration during stent implantation for malignant esophageal stricture

Abstract: Background:The rate of stent migration, especially in the short term after implantation, is high in the treatment process. We sought to explore an effective method for preventing early migration after stent implantation for malignant esophageal stricture and to provide the basis for clinical treatment. Methods:We conducted a prospective, open-label, parallel-assignment randomized controlled trial with patients undergoing stent implantation for malignant esophageal stricture. The proximal segments of stents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…In a randomized controlled trial, early stent migration did not occur in patients with malignant esophageal strictures when 2 TTS clips were symmetrically placed at the proximal end of the stent for fixation vs 14.6 of migration rate in the control group [6].…”
Section: Discussionmentioning
confidence: 95%
“…In a randomized controlled trial, early stent migration did not occur in patients with malignant esophageal strictures when 2 TTS clips were symmetrically placed at the proximal end of the stent for fixation vs 14.6 of migration rate in the control group [6].…”
Section: Discussionmentioning
confidence: 95%
“…Analogous techniques have been used with stents as an attempt to reduce stent migration rates, including utilizing metal endoscopic clips to attach the stent to the mucosa and transnasal sutures that attach at the proximal end of the stent, run proximally and out through the nose and are attached to the patient externally. 16,17 Endoscopically suturing the stents to the mucosa was used in our cohort in addition to clips and transnasal suturing. Because of the small number of patients in our cohort with fixation, it is not surprising that we were unable to discern a significant difference in migration rate.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies involving porcine models found that endoscopic sutures increased the force necessary to dislodge inserted SEMS, 19,20 while another 2 showed a reduction due to fixation in the clinical setting. 21,22 Furthermore, a recent randomized controlled study by Wang et al 16 found that stent fixation with metal clips is effective in preventing stent migration. While our study could not detect a benefit of utilizing fixation to prevent migration, there still may be a place for stent fixation and further prospective analysis with larger power is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 e). Esophageal stent migration is a common complication with an incidence of 14.6 % [1]. Distal migration of the stent can lead to complications such as intestinal obstruction and impaction [2,3].…”
mentioning
confidence: 99%